The end of social work. (3rd December 2020) - Maylea, Chris
Abstract: Social work literature is saturated with calls to reform social work in diverse and contradictory ways. This article argues that the profession of social work cannot be reformed and must be abolished. Specifically, the master narrative of Anglophone social work must be abandoned along with the institutions which maintain it; the professional bodies, the academic discipline and the formal title. Four reasons for this are presented: social work's lack of coherent theory base, the problem of professionalism, social work's historical abuses and the profession's inability to rise to contemporary challenges. The fundamental theoretical tensions in social work theory are identified as preventing the profession from reconciling its aims of assuaging individual suffering and achieving social justice. This has also hindered social work's aspiration to professionalism, which is both distracting and actively prevents social workers from working with people and communities. While these issues may have once been resolvable, the historical and contemporary contexts prevent resolution. Social work's uncertain theoretical foundations, desire for professional legitimacy, past abuses and contemporary failures put the profession beyond recovery. No solutions or resolutions are suggested. What pieces are to be salvaged from the wreck of social work must be determined by the post-social work world.